Sclerotherapy Induced Takotsubo Syndrome - Sunny Patel; Sepideh Nabatian; Michael Goyfman (Case Reports in Cardiology)
A 66-year-old female was brought to the emergency department for acute-onset left-sided chest pain. Prior to arrival, she was at an outpatient appointment with a vascular surgeon for elective sclerotherapy treatment of her lower extremity varicose veins. After receiving an IV injection of polidocanol, she developed severe chest pain with left arm and jaw numbness for the first time in her life. Upon arrival to the ED, the patient reported that her symptoms had resolved. Electrocardiogram (ECG) on presentation was significant for T-wave inversions in leads V1-V3. An initial set of cardiac enzymes showed a troponin I level of 0.62 ng/mL, which subsequently increased to 2.26 ng/mL. Her echocardiogram was significant for mild left ventricular systolic dysfunction with apical hypokinesis (ejection fraction 50%). A repeat ECG showed new T-wave inversions compared to that from the time of admission. The patient eventually agreed to cardiac catheterization, which revealed patent vessels without coronary artery disease, supporting our diagnosis of Takotsubo syndrome and what is the first reported case of likely polidocanol-induced Takotsubo syndrome in the United States.